The use of social networks in education : challenges and opportunities. - Othman, Abdul Rauf; Ali, Ahmad Salman; Ab Rahman, Mohd Faris; Muhammad, Muhd. Rosydi (IIUM Press, 2011)
Technology can have a reciprocal relationship with teaching. The emergence of new technologies pushes educators to understanding and leveraging these technologies for classroom use, at the same time, the on the ground implementation of these technologies in the classroom can directly impact how these technologies continue to take shape. Social network such as Friendster, MySpace, Facebook and twitter are popular and influential because they help satisfy the human need to create and connect. It is imperative that emergency communicators not only monitor the information shared across social media, but also engage the dialogue to help shape the conversation. Undoubtedly, without these recent technologies in the classroom, strong lessons can still be achieved, but there's a sharp disconnect between the way students are taught in school and the way the outside world approaches socialization, meaning making, and accomplishment